2016
DOI: 10.7705/biomedica.v37i2.2841
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors of cysticercosis in two rural communities from northern of Anzoátegui state, Venezuela

Abstract: Introducción. La cisticercosis es causada por larvas de Taenia solium, las cuales se localizan principalmente en el sistema nervioso central causando neurocisticercosis. En Venezuela se han realizado pocos estudios epidemiológicos.Objetivo. Determinar la seroprevalencia y factores de riesgo de cisticercosis en dos comunidades rurales del estado Anzoátegui, Venezuela.Materiales y métodos. Se hizo una encuesta donde se recogieron datos sobre los posibles factores de riesgo y signos y síntomas de la enfermedad y … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 21 publications
0
3
1
1
Order By: Relevance
“…In fact, other studies performed in Mozambique, Burkina Faso and Tanzania also found that seropositivity to cysticercal antigens was associated with severe headache [14,15,42,43]. Nevertheless, in other settings such as in Anzoa ´tegui in Venezuela, Vietnam and Nabo Village in Tiandong, China, no statistical association was found between these two variables [44][45][46]. Our findings may reflect the fact that headache may be correlated to the pathogenesis of the disease in this study setting.…”
Section: Cysticercosis Serology and Neuropsychiatric Disorderscontrasting
confidence: 59%
See 2 more Smart Citations
“…In fact, other studies performed in Mozambique, Burkina Faso and Tanzania also found that seropositivity to cysticercal antigens was associated with severe headache [14,15,42,43]. Nevertheless, in other settings such as in Anzoa ´tegui in Venezuela, Vietnam and Nabo Village in Tiandong, China, no statistical association was found between these two variables [44][45][46]. Our findings may reflect the fact that headache may be correlated to the pathogenesis of the disease in this study setting.…”
Section: Cysticercosis Serology and Neuropsychiatric Disorderscontrasting
confidence: 59%
“…To the contrary, in Tanzania [43], females were more likely to be seropositive, while in Burkina Faso and Vietnam this was true for males [29,58]. On the other hand, neither gender nor age presented a statistically significant association with seropositivity to cysticercosis in other studies [30,44,46,60].…”
Section: Risk Factors and Multivariate Logistic Regressionmentioning
confidence: 72%
See 1 more Smart Citation
“…encontraron una edad promedio de 37 años en México (12), en ambos casos población en edad laboral y en plena edad productiva. Entre los pacientes evaluados la mayor parte provenían del área rural con predominio de afiliación al régimen Fuente: elaboración propia subsidiado, lo que corresponde con un bajo estrato socioeconómico, lo cual es compatible con los factores de riesgo conocidos para la enfermedad (13,14). El ligero predominio femenino en nuestra muestra es consistente con otros estudios locales y regionales (15).…”
Section: Discussionunclassified
“…Cysticercosis is frequent in rural areas since it is associated with breeding of pigs under poor sanitary and environmental conditions, and low educational and socioeconomic level (Villalobos et al, 2007;Toquero, Morocoima & Ferrer, 2017;Maya et al, 2003). These conditions are all evidenced in María La Baja -Bolívar, since the highest educational level achieved by the majority of pig breeders (62%) was up to primary level, and their access to healthcare services was through subsidized regime.…”
Section: Discussionmentioning
confidence: 99%